2005
DOI: 10.2110/jsr.2005.015
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Kinetic Controls on Calcite Morphology in Supersaturated Solutions

Abstract: Recognizing microbial imprints in the morphology of calcium carbonate minerals that form in very supersaturated solutions containing a high level of dissolved inorganic carbon (DIC) is challenging. To better define criteria for this purpose, we have analyzed the influence of sulfate-reducing bacterium Desulfovibrio desulfuricans strain G20 on the morphology of calcite in such solutions. G20 does not induce large shifts of pH or alkalinity under these conditions, but its uptake of millimolar sulfate and lactate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 47 publications
4
69
0
Order By: Relevance
“…Calcification within these biofilms results from the complex interplay of metabolic and geochemical reactions occurring within and adjacent to the biofilm matrix, often in association with exopolymeric substances (Dupraz and Visscher, 2005;Altermann et al, 2006). The C, O, S, N, and Fe-based reduction-oxidation reactions that form the basis of microbial metabolisms greatly affect the biofilm system's pH, total alkalinity, and dissolved inorganic carbon, and thus [CO 2− 3 ] and CaCO3 of the biofilm's intercellular space, which determines whether calcification will occur (Bosak and Newman, 2005;Dupraz and Visscher, 2005;Visscher and Stolz, 2005;Baumgartner et al, 2006). Simplified examples (Visscher and Stolz, 2005) of such microbial reactions that effectively increase [CO …”
Section: Mechanisms Of Calcification Within Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calcification within these biofilms results from the complex interplay of metabolic and geochemical reactions occurring within and adjacent to the biofilm matrix, often in association with exopolymeric substances (Dupraz and Visscher, 2005;Altermann et al, 2006). The C, O, S, N, and Fe-based reduction-oxidation reactions that form the basis of microbial metabolisms greatly affect the biofilm system's pH, total alkalinity, and dissolved inorganic carbon, and thus [CO 2− 3 ] and CaCO3 of the biofilm's intercellular space, which determines whether calcification will occur (Bosak and Newman, 2005;Dupraz and Visscher, 2005;Visscher and Stolz, 2005;Baumgartner et al, 2006). Simplified examples (Visscher and Stolz, 2005) of such microbial reactions that effectively increase [CO …”
Section: Mechanisms Of Calcification Within Biofilmsmentioning
confidence: 99%
“…dissimilatory nitrate-reduction: Such primary microbial metabolic reactions within the biofilm are moderated by secondary reactions associated with exopolymeric substance (EPS; Reid et al, 2000;Arp et al, 2001;Bosak and Newman, 2005;Dupraz and Visscher, 2005). EPS is an extension of the microbial cell that maintains biofilm structure, establishes chemical microgradients by reducing rates of diffusion, may regulate intercellular processes, and functions to bind cations, elevate HCO − 3 , and nucleate CaCO 3 crystals (Arp et al, 2001;Dupraz and Visscher, 2005).…”
Section: Mechanisms Of Calcification Within Biofilmsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, organic molecules exuded by biofilms widely affect the precipitation of calcite, influencing not only the growth kinetics, but the morphology as well (Mann et al, 1990;Archibald et al, 1996;McGrath, 2001;Meldrum and Hyde, 2001;Braissant et al, 2003;Hammes et al, 2003;Tong et al, 2004;Bosak and Newman, 2005;Dupraz et al, 2009), likely through incorporation effects (Lowenstam and Weiner, 1989). Studies have also shown that various organic molecules widely affect the structure and morphology of a range of minerals, including numerous iron oxides (Châtellier et al, 2001(Châtellier et al, , 2004Larese-Casanova et al, 2010;Perez-Gonzalez et al, 2010), uranyl phosphate (Macaskie et al, 2000), and silica (Williams, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…This initiated predominantly rhombohedral calcite precipitation (Figure 6) at the same critical saturation state (S critical = 11 to 12) in the B. Pasteurii-inclusive and bacteriafree zone of the AGW, indicating the mineralogy and morphology of CaCO 3 precipitation is not controlled by B. Pasteurii surfaces and organic macromolecule exudates, which will be predominately contained within the dialysis membrane. Calcite formation is more likely to reflect the influence of organic and inorganic species slowing the rate of CaCO 3 precipitation (Kitano and Hood, 1965;Meldrum and Hyde, 2001;Braissant and Verrecchia, 2002;Braissant et al, 2003;Bosak et al, 2004;Bosak and Newman, 2005). Organic and inorganic species can complex with cations and reduce catatonic activity and decrease mineral supersaturation, or poison growth sites on the mineral surface (Meldrum and Hyde, 2001).…”
Section: Resultsmentioning
confidence: 99%